(untitled) (Socio-economic relations in the digital society, 2019)
Investigated the features state of the shadow economy in Ukraine and its development.Analyzed factors institutional functioning and prosperity of the shadow economy in Ukraine.Considered the various methodological and analytical approaches to assess the level of shadow economy.Identifi ed the place in the world rankings Ukraine, concerning the shadow economy.Grounded eff ect of the accumulation of factors infl uencing the level of shadow economy in Ukraine. Determined own interpretation of the concept of “incremental eff ect of factors infl uencing the level of the shadow economy of the state”. Proposed recommendations that will contribute to the reduction of the shadow economy in Ukraine. Represented the results of research in the form of conclusions.